2021
DOI: 10.1152/ajprenal.00204.2021
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian identification of candidate transcription factors for the regulation of Aqp2 gene expression

Abstract: Aqp2 gene transcription is strongly regulated by vasopressin in the renal collecting duct. However, the transcription factors (TFs) responsible for regulation of expression of aquaporin-2 (Aqp2) remain largely unknown. We used Bayes' Theorem to integrate several -omics datasets to stratify the 1344 TFs present in the mouse genome with regard to probabilities of regulating Aqp2 gene transcription. Also, we carried out new RNA-Seq experiments mapping the time course of vasopressin-induced changes in the transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…However, recent ChIP-seq analysis of the re-cloned mpkCCD cells that express all necessary molecular components for vasopressin signaling, AQP2 gene expression, and trafficking ( Rinschen et al, 2010 ; Xie et al, 2010 ; Khositseth et al, 2011 ; Schenk et al, 2012 ; Loo et al, 2013 ) showed no clear evidence of Creb1’s involvement in AQP2 transcription ( Jung et al, 2018 ). Instead, a number of other transcription factor candidates were suggested for future investigation ( Kikuchi et al, 2021 ), preferentially with CRISPR/Cas9-based gene knockout ( Isobe et al, 2017 , 2020 ; Datta et al, 2020 ) or small hairpin RNA-mediated gene knockdown when gene deletion is lethal ( Wang et al, 2017 , 2020 ; Kuo et al, 2018 ; Lin et al, 2019 ; Wong et al, 2020 ). Thus, a comprehensive AQP2 transcription network may be anticipated with the advent of the systems approaches that generate novel hypotheses addressable with modern molecular biological methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent ChIP-seq analysis of the re-cloned mpkCCD cells that express all necessary molecular components for vasopressin signaling, AQP2 gene expression, and trafficking ( Rinschen et al, 2010 ; Xie et al, 2010 ; Khositseth et al, 2011 ; Schenk et al, 2012 ; Loo et al, 2013 ) showed no clear evidence of Creb1’s involvement in AQP2 transcription ( Jung et al, 2018 ). Instead, a number of other transcription factor candidates were suggested for future investigation ( Kikuchi et al, 2021 ), preferentially with CRISPR/Cas9-based gene knockout ( Isobe et al, 2017 , 2020 ; Datta et al, 2020 ) or small hairpin RNA-mediated gene knockdown when gene deletion is lethal ( Wang et al, 2017 , 2020 ; Kuo et al, 2018 ; Lin et al, 2019 ; Wong et al, 2020 ). Thus, a comprehensive AQP2 transcription network may be anticipated with the advent of the systems approaches that generate novel hypotheses addressable with modern molecular biological methods.…”
Section: Discussionmentioning
confidence: 99%
“…The present study represents such an example. Previous system approaches have alluded to the role of glucocorticoid receptor in the Aqp2 gene expression in the kidney collecting duct cells ( Yu et al, 2009 ; Kikuchi et al, 2021 ). In line with this, glucocorticoid receptor agonist dexamethasone increases the vasopressin-induced Aqp2 gene expression in the collecting duct mpkCCD cells ( Kuo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent ChIP-seq analysis showed the indirect involvement of Creb1 in Aqp2 gene transcription ( Jung et al, 2018 ). A number of other transcription factor candidates were suggested for future investigation ( Kikuchi et al, 2021 ), preferentially with CRISPR/Cas9-based gene knockout ( Isobe et al, 2017 ; Datta et al, 2020 ; Isobe et al, 2020 ) or small hairpin RNA-mediated gene knockdown when gene knockout is lethal ( Wang et al, 2017 ; Kuo et al, 2018 ; Lin et al, 2019 ; Wang et al, 2020 ; Wong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As described above, the short-term effect of vasopressin is exerted by AQP2 translocation from the intracellular vesicles to the apical membrane. Furthermore, vasopressin can induce water reabsorption for 24 h or more by enhancing AQP2 transcription and its protein abundance in the collecting duct cells [ 16 , 17 ].…”
Section: Upon Vasopressin Stimulation Aqp2 Increases Water Reabsorption and Urine Concentrationmentioning
confidence: 99%